Exploring the emotional vocabulary of South African preschoolers and their stories about emotional situations, using a set of cartoon lion drawings - Briedenhann, Caitlin Grace (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.